Editorial Foreword For IKAT, Number 2 - Reid, Anthony (Center for Southeast Asian Social Studies (CESASS), 2018)
It is a pleasure to introduce this second issue of the enterprising new journal, IKAT. It is breaking new ground in opening Indonesia to its region, and establishing a high standard of scholarly publication in English. It is good to see Southeast Asians taking up the challenge of understanding their own region. As the Orientalist tradition of Europe weakens, institutions and individuals in the region must take up the challenge of understanding, preserving and analysing Southeast Asian cultures, many of them endangered. Southeast Asian Studies must return to Southeast Asia, and IKAT is certainly helping this process.